Photodynamic therapy for skin rejuvenation: treatment options – results of a consensus conference of an expert group for aesthetic photodynamic therapy. (8th May 2013) - Szeimies, Rolf‐Markus; Lischner, Stephan; Philipp‐Dormston, Wolfgang; Walker, Thorsten; Hiepe‐Wegener, Dagmar; Feise, Konstantin; Podda, Maurizio; Prager, Welf; Kohl, Elisabeth; Karrer, Sigrid
Summary In addition to providing effective treatment for non‐melanoma skin cancers or their precursors, photodynamic therapy (PDT) has also attracted considerable attention for its use on aesthetic dermatology. In a first consensus publication the mechanisms of action of its photorejuvenation effects and recent studies were presented; in this paper treatment protocols for the different anatomical regions exposed to chronic sun damage like face, neck, décolleté and the back of the hands are given and suitable procedures for pre‐ and after‐care are discussed.